2014
DOI: 10.1007/s00345-014-1383-5
|View full text |Cite
|
Sign up to set email alerts
|

Mixed low- and high-grade non-muscle-invasive bladder cancer: a histological subtype with favorable outcome

Abstract: Mixed low- and high-grade NMIBC exhibits a significantly better response profile to intravesical BCG therapy compared to PHG NMIBC. The implications of these results are that less aggressive treatment strategies for this unique cancer entity may be needed and that there is a benefit to the reporting of tumor heterogeneity in transurethral resection of bladder tumor specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Three recent publications have suggested that urothelial carcinomas with grade heterogeneity have a prognosis more in keeping with low‐grade carcinomas based on time to recurrence and disease‐free survival. However, previous literature has suggested that molecular markers may predict tumour behaviour more accurately than conventional histology .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Three recent publications have suggested that urothelial carcinomas with grade heterogeneity have a prognosis more in keeping with low‐grade carcinomas based on time to recurrence and disease‐free survival. However, previous literature has suggested that molecular markers may predict tumour behaviour more accurately than conventional histology .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous literature has suggested that molecular markers may predict tumour behaviour more accurately than conventional histology . In all papers, carcinomas were categorized based on morphology alone. A different cut‐off was utilized in determining grade heterogeneity in each paper (<50%, <10% and <5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors recommend that patients with high-grade T1 disease and LVI consider early cystectomy to preserve their chance for cure [26]. On the other end of the risk continuum are patients with mixed high-grade and low-grade NMIBC, an entity which Schubert et al [27] report is less aggressive than high-grade NMIBC alone and is less likely to require advanced intervention with radical cystectomy or non-BCG intravesical agents.…”
Section: Risk Stratificationmentioning
confidence: 95%